Dynamic enhancement in adhesion forces of truncated and nanosphere tips on substrates. Issue 111 (26th October 2015) - Zhou, Hongjun; Xu, Quan; Li, Shaowei; Zheng, Yanjun; Wu, Xu; Gu, Chaokang; Chen, Yusheng; Zhong, Jian
Abstract : Both AFM tip shape and substrate have obvious effects on the dynamic adhesion forces of truncated and nanosphere tips on four different substrates (mica, sapphire, silicon wafer, and highly oriented pyrolytic graphite). Abstract : The understanding of the attachment and detachment of micro/nanomaterials to and from a substrate can benefit a wide range of interfacial scientific fields. Here, we fabricated two types of AFM tips: a nanosphere tip with a SiO2 nanoparticles having a diameter of 980 nm to the AFM tip and truncated tip with a triangular surface having a side length of 959 nm at the end of the AFM tip. Then we studied the dynamic adhesion enhancement using AFM. When the retraction velocity increased from 0.02 μm s −1 to 156 μm s −1, the adhesion force of the two tips to four different substrates significantly increased and the highest increase was on a sapphire substrate. The order of the adhesion forces of nanoscale samples (nanosphere tip and truncated tip) from different substrates was: HOPG > silicon wafer > mica > sapphire, which is reversely consistent with that of the Young's modulus of the substrates. In addition, the dynamic forces of the truncated tip were larger than those of the nanosphere tip. Therefore, the tip shape and substrate had obvious effects on the dynamic adhesion forces. However, the modelling results showed that both the tip shape and substrate type had no obvious effect on the dynamic scaling parameters n and dynamic coefficient parameter C . Our work provides useful information for analyzing the interactions between micro/nanomaterials and their environments. It benefits the understanding of numerous natural phenomena and the development of artificial micro/nanomaterials.